Program Standards and Accreditation in the Teacher Education - Abdullah ADIGÜZEL; Mustafa SAĞLAM (İnönü Üniversitesi Eğitim Fakültesi Dergisi)
In this article, based on the sources and researches related with the quality standards, it is aimed at describing the importance of quality standards in teacher training. Thus, in this article, firstly the necessity of developing standards, the steps of developing these standards in teacher training, current studies in the USA, England, and Turkey, secondly the relationship between goals, accreditation and quality teacher training and lastly the aim and benefits of developing standards in teacher training are described. As a result, since developing standards in Teacher Training means quality assurance, quality standards are used to accredit the productivity of an educational program which prepares candidate teacher for becoming teacher